The hidden curriculum across medical disciplines: an examination of scope, impact, and context - Schultz, Karen; Cofie, Nicholas; Braund, Heather; Joneja, Mala; Watson, Shayna; Drover, John; MacMillan-Jones, Laura; Dalgarno, Nancy (Canadian Medical Education Journal, 2023)
Background: While research suggests that manifestations of the hidden curriculum (HC) phenomenon have the potential to reinforce or undermine the values of an institution, very few studies have comprehensively measured its scope, impact, and the varied clinical teaching and learning contexts within which they occur. We explored the HC and examined the validity of newly developed constructs and determined the influence of context on the HC. Methods: We surveyed medical students (n =182), residents (n =148), and faculty (n = 140) from all disciplines at our institution between 2019 and 2020. Based on prior research and expertise, we measured participants’ experience with the HC including perceptions of respect and disrespect for different medical disciplines, settings in which the HC is experienced, impact of the HC, personal actions, efficacy, and their institutional perceptions. We examined the factor structure, reliability, and validity of the HC constructs using exploratory factor analysis Cronbach’s alpha, regression analysis and Pearson’s correlations. Results: Expert judges (physician faculty and medical learners) confirmed the content validity of the items used and the analysis revealed new HC constructs reflecting negative expressions, positive impacts and expressions, negative impacts, personal actions, and positive institutional perceptions of the HC. Evidence for criterion validity was found for the negative impacts and the personal actions constructs and were significantly associated with the stage of respondents’ career and gender. Support for convergent validity was obtained for HC constructs that were significantly correlated with certain contexts within which the HC occurs. Conclusion: More unique dimensions and contexts of the HC exist than have been previously documented. The findings demonstrate that specific clinical contexts can be targeted to improve negative expressions and impacts of the HC.